Fostering a global talent mindset for young entrepreneurs in Malaysia (tertiary level) - Ab Aziz, Nur Hafizah; Ibrahim, Nurhanim; Meor Mahaputra, Mai Tiara Alia; Wan Kefli, Wan Fatanah Syaza; Mohamed Ayub, Noor Halimatun Saadiah; Abdul Karim, Suraya; Ramli, Suriana (Universiti Teknologi MARA, Kedah, 2023)
The world is becoming more interconnected and globalized, and as a result, instilling a mindset of global talent in young students is essential for achieving success in the competitive modern business environment. Students entering tertiary Education in Malaysia are strongly encouraged to develop this talent attitude as soon as feasible. If they develop a talent mindset, these aspiring young business owners will have the skills and knowledge required to compete successfully in a global market. In this study, we offer a framework that can further speed the process of shifting the global mindset through enhancing knowledge and skill as well as enriching experience gained in real-world settings. If they do so, the next generation of aspiring entrepreneurs will have a better chance of succeeding in the business markets of the world. It is possible to realize the goals of accelerating the transformation of tertiary Education in generating future entrepreneurs if there is active collaboration between the government, higher institutions, and businesses. These goals are in parallel with the economic policy of Malaysia.